Photoinduced energy-transfer in covalently and non-covalently linked supramolecular arrays of metal polypyridyl complexes - Michael D. Ward (International Journal of Photoenergy)
Photoinduced energy-transfer has been studied between the component parts of two types of multichromophoric array. In the first type the components (metal polypyridyl complexes) are covalently linked by using the bridging ligand 2,2′:3′,2″:6″,2′″-quaterpyridine, which has two inequivalent bipyridyl chelating sites in close proximity. Structural, redox and photophysical studies of the complexes based on this ligand show how the properties of each metal fragment vary between the two inequivalent binding sites, and show also how efficient inter-component energy transfer can occur between components, with an example of the antenna effect being demonstrated by energy transfer from three peripheral {Re(bipy)(CO)3CL} fragments to one central {Ru(bipy)3}2+ fragment. In the second type of supramolecular array, the mononuclear complex component parts are held together by hydrogen-bonding between peripheral adenine, thymine, cytosine or guanine nucleobase groups. Thus a {Ru(bipy)3}2+ derivative with a pendant cytosine group strongly associates in CH2CL2 solution with an {Os(bipy)3}2+ complex bearing a pendant guanine group, by Watson-Crick base-pair formation (Ka≈5000M-1), and Ru→Os photoinduced energy-transfer can occur across the triple hydrogen-bonded bridge.